Transformation of stereotypical perception of „the image of Poles” in the Russian Empire society during the World War I - Olga Bilobrovets (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2017)
Transformation of stereotypical perception of „the image of Poles” in the Russian Empire society during the World War I